2014
DOI: 10.1093/ageing/afu174
|View full text |Cite
|
Sign up to set email alerts
|

The second national audit of intermediate care

Abstract: Intermediate care services have developed internationally to expedite discharge from hospital and to provide an alternative to an emergency hospital admission. Inconsistencies in the evidence base and under-developed governance structures led to concerns about the care quality, outcomes and provision of intermediate care in the NHS. The National Audit of Intermediate Care was therefore established by an interdisciplinary group. The second national audit reported in 2013 and included crisis response teams, home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 7 publications
1
29
0
5
Order By: Relevance
“…The American post-acute care case acceptance standards based on the post-acute care DRG systems led to significantly different groups of patients receiving care than under the intermediate care system of the UK. 17,18) Although numerous studies have confirmed that aging will increase medical expenditures, 19) National Beds Inquiry report of the UK in 2000 found that, despite the continuous increase in the country's older population starting in the 1980s, the number of acute hospital beds and days of patient hospitalization has in fact fallen steadily. The strict control of the number of days of hospitalization led to a very high percentage of older adults whose cognitive and physical function had not appropriately recovered being transferred to long-term care facilities.…”
Section: Development Of Post-acute Carementioning
confidence: 99%
“…The American post-acute care case acceptance standards based on the post-acute care DRG systems led to significantly different groups of patients receiving care than under the intermediate care system of the UK. 17,18) Although numerous studies have confirmed that aging will increase medical expenditures, 19) National Beds Inquiry report of the UK in 2000 found that, despite the continuous increase in the country's older population starting in the 1980s, the number of acute hospital beds and days of patient hospitalization has in fact fallen steadily. The strict control of the number of days of hospitalization led to a very high percentage of older adults whose cognitive and physical function had not appropriately recovered being transferred to long-term care facilities.…”
Section: Development Of Post-acute Carementioning
confidence: 99%
“…46 We believe that our finding regarding reablement services (no completed RCTs or CCTs) is robust, due to the use of systematic review techniques. We accept that there are services calling themselves reablement services that do not fit the definition we used, such as those using health professionals rather than home care 47 and our findings do not apply to other variants of intermediate care such as health service based admission avoidance and early discharge services that have evidence, including evidence of some benefits such as reduced use of long term care and reduced hospital length of stay [48][49][50] .…”
Section: Discussionmentioning
confidence: 99%
“…Because they defy the existing, disease‐specific organization of the healthcare system, frail individuals commonly are poorly served and therefore receive inadequate care. For example, a recent report by the National Health Service in the United Kingdom suggested that hospital care is so hazardous for older, frail adults that alternatives are needed …”
Section: Integrating Frailty Research Into the Specialties: Gaps And mentioning
confidence: 99%